Analisis Mineral Tanah Rawan Longsor Menggunakan X-Ray Diffraction Di Desa Sawaru Kabupaten Maros - Rahmaniah Rahmaniah; Reskywijaya Reskywijaya; Ayu Sari Wahyuni; Harsano Jayadi (Universitas Negeri Gorontalo, 2020)
The study of soil minerals structure has been conducted in the Sawaru village, Maros regency, South Sulawesi which is locally known to be the landslides-prone area. The aim of this research is basically to determine the mineral characteristics of the soil. The samples were taken randomly in three points with a depth of 75 cm at point 1 and 100 cm for the other. The structure of the samples was analyzed using X-Ray Diffraction (XRD) where the samples were placed in the high temperature and airtight containers. The results of XRD analysis showed that minerals contained at point 1 (75 cm in depth) were illite (69.3%) with a monoclinic structure, albit mineral (25.6%) with a triclinic structure and kaolinite (5.0%) with a triclinic structure. Samples at point II (100 cm depth) contained illite (67.2%), feldspar (23.9%) with monoclinic and merrillit (8.9%) with trigonal structures. Samples at point III (100 cm in depth) contained illite (55.9%), bobtraillite (22.2%) with a trigonal structure and feldspar (21.9%) with a monoclinic structure. The minerals observed at the sampling points are dominated by illite which is clay in nature. Such a mineral has been known to have an ability to initiate high plasticity in soil, leading to the slope instability.